PERLINDUNGAN HUKUM TERHADAP WARGA NEGARA INDONESIADARI AKIBAT PERJANJIAN PERKAWINAN PADA PERKAWINAN CAMPURAN(STUDI PUTUSAN MAHKAMAH KONSTITUSI RI NOMOR 69/PUU-XIII/2015) - DANIEL JEFFREY LUMBAN BATU (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Hasim Purba, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Yefrizawati, SH, MHum The research results demonstrate that before the enactment of the Verdict of the Constitutional Court No. 69/PUU-XIII/2015, the law is considered incapable of insuring the constitutional rights of Indonesian citizens who are married to foreign citizens without a marital agreement. The Verdict of the Constitutional Court has widened the significance of a marital agreement so that it is not only interpreted as an agreement made before or by the time of the marriage, but it can also be made during the marriage. A marital marriage is highly needed by Indonesian citizens who are married to foreign citizens in order to provide protection, insurance, and legal benefits for all parties unexceptionally the third party outside the marriage. The verdict is not only beneficial for those in a mixed marriage, but also for all married couples.Keywords: Legal Protection, Indonesian Citizens, Marriage, Marital Agreement, Mixed Marriage, Foreign Citizens.